Investigating new media technology adoption and challenges among agricultural extension agents in Yemen - Saeed, Ali Abdullah Mohammed (2019)
The new media can improve farmers’ access to extension service. However, little evidence was shown from research on new media technology adoption among extension agents for communication with farmers. The objectives of this study are to identify frequent social media tool knowledge workers use to contact farmers, investigate social media communication between knowledge workers and farmers, identify barriers of new technology use for information seeking and explore how the new technology may improve knowledge transfer to farmers. This study investigates the issue using in-depth interviews among 12 public agricultural extension agents in Dhamar district of Yemen. Participants’ job experience ranges from over 20-year to newly workers with less than three months at work. They work in different types of farming knowledge communication known as extension involving crop production, plant protection, breeding and expansion management. Thematic analysis was employed to analyze the data using NVivo 12 pro software for qualitative data. The WhatsApp was found to be the most frequent social media tool among the participants for contact with farmers. Half of the participants use the new media technology to advise farmers on plant disease diagnosis. Illiteracy among farmers, poor Internet infrastructure, lack of funding, and political unrest were reported as key challenges to social media use for extension communication. However, the participants reported that social media are easy to use, save time, enable immediate troubleshooting, and represent an inexpensive method to access farmers. Evidence based result on technology use by extension agents for contact with farmers might help extension organizations to consider social media integration within outreach extension methods. It provides an empirical scale based on the Uses and Gratification Theory for exploring actual social media usage for extension communication. It also presents a barrier model based on the Technology Acceptance Model and the Unified Theory of Acceptance and Use of Technology (UTAUT) for understanding challenges to the new media use for extension communication.